A šta bi tek Haksli rekao na to! (Kako je Vrli novi svet u romanu Mali je svet postao "veličanstven") (Philologia, 2021)
The author of this paper systematically analyses innumerable mistakes made in the Serbian translation of the novel Small World written by David Lodge, and evaluates the target text by its comparison with the source text. The aim of the research is to indicate why Serbian literary translators encounter certain problems, as well as to prove that much more attention should be paid by our publishers to this matter, in order to improve the final product of translation before it is presented to the readers.